3D printed waveguide step‐twist with bandpass filtering functionality. Issue 11 (1st May 2020) - Zhang, Yi; Zhang, Fan; Gao, Yang; Xu, Jun; Guo, Cheng; Shang, Xiaobang
Abstract : A novel waveguide step‐twist integrated with a bandpass filter is presented in this Letter. The twist is composed of four equally rotated cavities to achieve polarisation rotation and filtering functionalities simultaneously. Such step‐twist can achieve a significant reduction in size and weight. The design is demonstrated at Ka‐band using waveguide technology and is fabricated using a stereolithography apparatus 3D printing together with metal plating. The device is designed to have a centre frequency of 32 GHz and a bandwidth of 1 GHz. The measured result shows good agreement with simulations, with a measured average insertion loss of 0.84 dB and a return loss better than 15 dB across the passband.